Visions of the 21st century family transforming structures and identities - Claster, Patricia Neff.; Blair, Sampson Lee. (Bingley, U.K. : Emerald, 2013)
One undeniable fact about families is that they keep changing, both in terms of structure and behavior. Many factors have served to bring about such changes, including social, cultural, political, and institutional change, resulting in family forms which perhaps may represent the new traditional in the not-so-distant future. Through research studies from around the world, this volume examines these changing structures and behaviors, and attempts to better illustrate the ever-changing nature of families. Topics covered include: transracial adoption, lesbian parenting, intergenerational relationships, procreative identities, ex-spouse relationships, military couples, the meaning of remarriage, and gender roles within contemporary families, among other topics. This volume, along with future volumes of CPFR, utilizes a wide variety of methodological and theoretical approaches, and attempts to provide a comprehensive examination of change in family structures and behaviors.
Making sense of donors and donor siblings : a comparison of the perceptions of donor-conceived offspring in lesbian-parent and heterosexual-parent families / Margaret K. Nelson, Rosanna Hertz, Wendy Kramer -- Emotion work in black and white : transracial adoption and the process of racial socialization / Cardell K. Jacobson, Darron T. Smith -- "We are both her mothers and I want the world to know that" : parent term selection among lesbian co-parents with children conceived through donor insemination / Rafael J. Colonna -- The hands that (yet) rock the cradle : unveiling the social construction of the family through the contemporary birthing ritual / Rosalina Pisco Costa -- The process through which men and women construct procreative identities : a narrative approach / Tamara G. Coon Sells -- Recent economic distress in midlife : consequences for adult children's relationships with their mothers / Megan Gilligan, J. Jill Suitor, Karl Pillemer -- Subjective preferences versus objective realities : voices of full- and part-time employed mothers / Pamela Aronson, Jeylan T. Mortimer -- On the fast track : dual military couples navigating institutional structures / David G. Smith, Mady Wechsler Segal -- "Small house" practice and its impact on the traditional family unit in Zimbabwe / Lovemore Ndlovu -- Negotiating family challenges by transforming traditional gender roles in new identities : patterns of resilience and parenthood in a sample of Italian couples / Giovanna Gianesini -- The Schism of "ISMS" : how race, class, gender, and sexuality impact the adoption triad in the United States / Pamela Ray Koch, John Carl Koch -- Caregiving for an ex-husband : exploring precipitating factors and relational outcomes / Christine M. Proulx ... [et al.] -- You are my world : the social embeddedness of remarriage / Muh-Chung Lin -- Defining family : perspectives of homeless adults in southeast Texas / Janeal M. McCauley ... [et al.] -- On generations, affections, and roles in the family in Brazil / Alda Britto da Motta.
Print version record
Keywords: Social Science -- Sociology -- Marriage & Family; Family & Relationships -- Family Relationships; Sociology: family & relationships; Sociology; Families